Using Video with Caption Modes to Improve Vocabulary Learning for Students at a Primary School in Vietnam = Sử dụng Video có phụ đề để cải thiện việc học từ vựng cho học sinh tại một trường tiểu học ở Việt Nam. M.A. Thesis. English Linguistics: - Nguyễn, Thị Nụ (2019)
Vocabulary is one of the most important parts of language learning and teaching. Being an English teacher in a primary school, I deeply understand and sympathize with difficulties that students usually encounter in study and use of English vocabulary. Additionally, vocabulary classes are also quite boring with traditional teaching methods. Using video in teaching English is also a new and modern method. However, when students watch teaching videos provided by teachers, they grasp very poorly. Obviously, it is necessary to find out an effective way to improve vocabulary learning for students in English lessons by using video with caption modes.